INDIVIDUAL AND CREATIVE DEVELOPMENT OF THE FUTURE TEACHERS - THE WAY TO PREPARE HIGHLY QUALIFIED SPECIALISTS (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to individual creative development of future teachers in conditions of professional teaching.
Keywords: 1